Impact of Additional Physical Activity Program on Motor Abilities Development in School Children - Vanja Popovic; Fitim Arifi; Boris Zarkovic; Marin Corluka (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
The aim of this study is to determine there is a statistically significant difference in motor ability indicators in children of early school age before and after the defined experimental process. The total number of subjects is 40 and the subjects was divided into two subsamples: a subsample of boys (n = 20) with an average age of 6.20 ± 0.34 years and a subsample of a girls (n = 20) with an average age of 6.16 ± 0.62 years. All subjects were participants in the program of the sports school of the children fitness centre Smart Gym from Podgorica. Subsamples were subjected to an experimental process lasting 8 weeks. Immediately before and after the experimental process, motor abilities were measured using the following 10 tests: 5m sprint, 10m sprint, standing long jump, polygon backwards, bent arm hang, sit and reach, climbing and descending, stork balance stand test, sit ups, and throw and catch test. The results of the study show that the experimental process was successful in improving the polygon backwards, forward deep bend and throw and catch test in boys and stork balance stand test, sit ups and throw and catch test in girls. Such a program could improve the working methodology in all sport schools throughout Montenegro.